Structural Analysis and Synthesis : A Laboratory Course in Structural Geology - Rowland, Stehen M.; Duebendorfer, Ernest M.; Schiefelbein, Ilsa M. (Oxford : Blackwell, 2007)
This widely used, highly readable introduction to structural analysis is specifically designed to support the laboratory work of undergraduates in structural geology courses. Throughout the book, a geologic map from a mythical site, the Bree Creek Quadrangle, is used to help students analyze various aspects of the geologic structures exposed within this quadrangle, and ultimately to combine these analyzes into a grand synthesis.Guided by students' and instructors' suggestions, the authors have refined several exercises and added new ones for this third edition. In addition, every figure has been redrafted to improve clarity, and the Bree Creek Quadrangle map has been compiled onto a single fold-out sheet. An instructor's manual is available on request from the publisher to assist the laboratory instructor in the use of the book.
Includes References 289-290p.; Further reading 291-296p.; Index 297-301p.
Keywords: Laboratory Manuals; Structural geology; Geology